“TÔ VELHA, MAS NÃO TÔ MORTA”: UM OLHAR ANTROPOLÓGICO SOBRE MULHERES QUE PARTICIPAM DO PROJETO UNIVERSIDADE ABERTA À PESSOA IDOSA DA UFMS - JULIANA CRISTINA DOS SANTOS DUARTE (2021)
ABSTRACT The present dissertation aims to construct an analysis of the place given to education by women who are experiencing old age. The desire to be in a social space like the university, ends up constituting the resignification of that space. For the analysis, we have as interlocutors elderly women participating in the Open University for the Elderly - UNAPI / UFMS, who chose among the activities offered by the institutional program to participate in undergraduate courses. At first, the importance of the intersectional discussion between aging and gender was perceived as a way of contextualizing the dynamics experienced by women. The main objective of the research is to understand what makes women, already in old age, choose as an activity to enter the dynamics of academic life. In this sense, we sought to problematize the aging trajectories of women who encourage the desire to continue studying in old age. As it is a study from UNAPI, our interlocutors are women over 60 years old, from different layers of society, who, at least, enrolled in undergraduate subjects offered by UNAPI from 2019 - 2020. The approach focuses on understanding the particularities of the course of life, from the apprehension of their narratives. Thus, the research used, theoretically and methodologically, an ethnographic bias, through informal conversations and semi-structured interviews starting from specific topics about the aging trajectories of these women, as well as their specificities. Keywords: aging; women; memory; course of life; UNAPI.